Nonlinear Finite Analysis of Structural Behavior of Brick Masonry-Infilled Reinforced Concrete Frames - Kori Effendi, Mahmud; Hardawati, Astriana; Masjuki, Siti Aliyyah (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
Earthquake disasters are one source of disaster that often causes buildings to experience total collapse or partial damage so that the structure may no longer be usable. Brick masonry wall construction, both unreinforced and reinforced masonry walls, is starting to be widely used in the world. To study and interpret the behavior of brick walls under various loads, the numerical modeling approach offers a cheaper way to understand the structural response accurately compared to experimental approaches which require greater costs. Three-dimensional finite element analysis of masonry walls was performed using MSC. Marc/Mentat software to verify the analysis results with experimental results on brick masonry walls with concrete frame constraints. For brick walls, concrete frames are modeled with 3D solid elements, while reinforcing steel uses 3D truss elements. The strain stress is multi-linear for concrete and bi-linear for reinforcing steel. The modified Kent–Parker model was used to model the multi-linear stress-strain of the macro element of a brick wall. The Linear Mohr-Coulomb plasticity and the flow plasticity of the isotropic hardening rule were used for concrete and brick walls. Contact analysis was carried out between both concrete beams and concrete columns with walls. The loading was applied in the plane with the force control. The result of the analysis shows that the deformed shape of the brick wall is different from the experimental results because of the complexity of contact analysis and the macro element modeling of brick elements. The contact that occurs shows that there is no separation between the brick wall and the concrete frame. Based on the results of finite element analysis, the initial stiffness is the same between the finite element analysis result and the experimental result.